2017
DOI: 10.1055/s-0037-1602835
|View full text |Cite
|
Sign up to set email alerts
|

Dysarthria of Spinal Cord Injury and Its Management

Abstract: The dysarthria associated with spinal cord injury (SCI) is characterized by speech impairments that reflect respiratory dysfunction and its downstream effects on phonation, articulation, and prosody. The exact nature of the dysarthria is determined in large part by the level of SCI and whether or not diaphragm function is spared. Individuals with insufficient diaphragm strength to breathe on their own must rely on ventilator support, which may help or hinder speech, depending on a variety of ventilator-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Although a small number of reviews and studies on voice and respiratory function in people with CSCIs have been reported, there are no reports on their relationships with voice user interfaces [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Although a small number of reviews and studies on voice and respiratory function in people with CSCIs have been reported, there are no reports on their relationships with voice user interfaces [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%